Prevalence and predictors of small intestinal bacterial overgrowth in inflammatory bowel disease: a meta-analysis - Feng, Xin; Hu, Jie; Zhang, Xin (Frontiers in Medicine, 2025)
BackgroundSmall intestinal bacterial overgrowth (SIBO) has been reported to be very common among individuals with inflammatory bowel disease (IBD), and the prevalence of SIBO is highly variable. We conducted this study to calculate the prevalence and identify predictors of SIBO in IBD.MethodsPubMed, Cochrane Library, and EMBASE from inception to March 2024 were searched for studies evaluating the prevalence of SIBO in IBD. We calculated the pooled prevalence of SIBO among IBD patients and the odds ratio (OR) of SIBO in IBD compared with healthy controls. Besides, we also evaluated predictors of SIBO in IBD patients.ResultsTwenty-nine studies (3,250 IBD, 708 controls) were included in our study. The pooled prevalence of SIBO in IBD was 31.0% (95% CI 25.2–37.1), and the prevalence of SIBO was higher in IBD compared with healthy controls (OR 5.25, 95% CI 2.96–9.32). The pooled prevalence of SIBO was higher among CD patients (32.2, 95% CI 25.9–38.8) compared with UC patients (27.8, 95% CI 18.5–38.1). The odds of lower BMI (mean difference = −1.04; 95% CI −1.86 to −0.23), bloating (OR = 3.02, 95% CI 1.22–7.5), flatulence (OR = 4.70, 95% CI 1.44–15.35), history of abdominal surgery (OR = 2.05, 95% CI 1.35–3.11), and stricturing/penetrating disease behavior (OR = 3.51, 95% CI 1.67–7.40) increased significantly in IBD patients with SIBO compared to those without SIBO. Antibiotic treatment may be effective for SIBO in IBD patients.ConclusionNearly one-third of IBD patients present with SIBO positive, and the odds of SIBO in IBD was increased by 5.25-fold compared with healthy controls. Lower BMI, bloating, flatulence, history of abdominal surgery, and stricturing/penetrating disease behavior were predictors of SIBO in IBD patients.